Far-infrared properties of submillimeter and optically faint radio galaxies - Magnelli, B; Lutz, D; Berta, S; Altieri, B; Andreani, P; Aussel, H; Castañeda, H; Cava, A; Cepa, J; Cimatti, A; Daddi, E; Dannerbauer, H; et al. (2010)
We use deep observations obtained with the Photodetector Array Camera and Spectrometer (PACS) onboard the Herschel Space Observatory to study the far-infrared (FIR) properties of submillimeter and optically faint radio galaxies (SMGs and OFRGs). From literature we compiled a sample of 35 securely identified SMGs and nine OFRGs located in the GOODS-N and the A2218 fields. This sample is cross-matched with our PACS 100 μm and 160 μm multi-wavelength catalogs based on sources-extraction using prior detections at 24 μm. About half of the galaxies in our sample are detected in at least the PACS 160 μm bandpass. The dust temperatures and the infrared luminosities of our galaxies are derived by fitting their PACS and SCUBA 850 μm (only the upper limits for the OFRGs) flux densities with a single modified (β = 1.5) black body function. The median dust temperature of our SMG sample is Tdust = 36±8 K while for our OFRG sample it is Tdust = 47±3 K. For both samples, median dust temperatures derived from Herschel data agree well with previous estimates. In particular, Chapman et al. (2005, ApJ, 622, 772) found a dust temperature of Tdust = 36±7 K for a large sample of SMGs assuming the validity of the FIR/radio correlation (i.e., q= log 10(LFIR[W]/L1.4GHz[W Hz -1] /3.75×1012)). The agreement between our studies confirms that the local FIR/radio correlation effectively holds at high redshift even though we find q = 2.17±0.19, a slightly lower value than that observed in local systems. The median infrared luminosities of SMGs and OFRGs are 4.6×1012 Lȯ and 2.6×1012 andLȯ, respectively. We note that for both samples the infrared luminosity estimates from the radio part of the spectral energy distribution (SED) are accurate, while estimates from the mid-IR are considerably (∼×3) more uncertain. Our observations confirm the remarkably high luminosities of SMGs and thus imply median star-formation rates of 960 Mȯ yr-1 for SMGs with S(850 μm)>5 mJy and 460 Mȯ yr-1 for SMGs with S(850 μm)>2 mJy, assuming a Chabrier IMF and no dominant AGN contribution to the far-infrared luminosity. © 2010 ESO.